Injury, illness, and medication use surveillance during the 2020 COSAFA Women`s championship: a prospective cohort study of football players from Southern Africa - Mkumbuzi, N. S.; Dlamini, S. B.; Chibhabha, F.; Govere, F. M. (Science and Medicine in Football, 2023)
Background: Systematic analyses of injuries, illnesses or medication use and their risk factors among female African athletes are scarce, which has implications for management of these athletes. Aim: This prospective cohort study analysed the incidence and characteristics of injuries, illnesses and medication use during the 2020 COSAFA Women`s Championship. Methods: The medical personnel of all participating teams reported all new injuries, illnesses and medication used by players daily. Results: Sixty-three injuries were reported: 45 match and 18 training injuries; 45.5 (95% CI: 32.2 to 58.8) injuries/1000 match-hours and 21.7 (95% CI: 11.7 to 31.7) injuries/1000 training-hours, respectively. Most (n = 55, 87%) were caused by contact with another player and involved the lower extremity (n = 43; 68%). Fifty-eight illnesses were reported: 44.4 (95% CI: 33.0 to 58.8) illnesses/1000 player-days, mostly diarrhoea (n = 25; 43.1%) and dysmenorrhoea (n = 18; 31%). No cases of COVID-19 were reported. In total, 175 medications were prescribed: 168.8 (95% CI: 143.8 to 193.8) medications/1000 player-days. Non-steroidal anti-inflammatory drugs (NSAIDs) (n = 60; 34.3%) and analgesics (n = 33; 18.9%) were the most commonly prescribed drugs. Conclusion: Incidences of injury and illnesses were high but time loss was low, likely due to high NSAIDs use. Further studies should be conducted in order to inform appropriate prevention or management protocols in this population.